2014
DOI: 10.1177/0956462414532447
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of prevalent sexually transmitted infections among participants screened for an HIV incidence cohort study in Kisumu, Kenya

Abstract: Background We determined the prevalence of four sexually transmitted infections and the demographic and behavioural correlates associated with having one or more sexually transmitted infections among participants in an HIV incidence cohort study in Kisumu, western Kenya. Methods Participants were enrolled from a convenience sample and underwent aetiologic sexually transmitted infection investigation. Demographic and behavioural information were collected and basic clinical evaluation performed. Multiple regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Our study suggested that females who were divorced or widowed had a higher probability of HSV-2 infection. Several other surveys have also shown the same relationship between marital status and HSV-2 infection, particularly for females [3, 26, 27]. A study from Tanzania showed that females who were divorced or widowed may engage with multiple sex partners due to relative personal freedom and in an attempt to establish new relationships [27].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our study suggested that females who were divorced or widowed had a higher probability of HSV-2 infection. Several other surveys have also shown the same relationship between marital status and HSV-2 infection, particularly for females [3, 26, 27]. A study from Tanzania showed that females who were divorced or widowed may engage with multiple sex partners due to relative personal freedom and in an attempt to establish new relationships [27].…”
Section: Discussionmentioning
confidence: 90%
“…A study from Tanzania showed that females who were divorced or widowed may engage with multiple sex partners due to relative personal freedom and in an attempt to establish new relationships [27]. Another study from Kenya inferred that some of such females may experience significant pressure due to childrearing and few skills to earn money, thus some of them may resort to transactional sex [26]. However, the reason why females who were divorced or widowed had a relatively higher seroprevalence of HSV-2 infection in Shandong still need further research.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Following age-related trends in HIV, in western Kenya HSV-2 prevalence increases dramatically from 10% in 13- to 14-year-old girls to 28% in 15- to 19-yearolds. 12,13 Bacterial vaginosis (BV) affects over 20% of general population women in Kenya 14,15 and up to 40% of women with HIV or in clinic-based settings. 1618 Given the high burden of HIV and sexually transmitted infection (STIs), SQoL may be adversely affected.…”
Section: Introductionmentioning
confidence: 99%
“…HSV-2 is the most common cause of genital ulcer disease worldwide, the most prevalent STI in sub-Saharan Africa, and a well-established biomarker for sexual risk behaviour [8, 33, 34]. Evidence suggests HSV-2 prevalence in girls in the study area increases from 10% in 13-14 yr. to 28% in 15-19 yr., and 70% among the 20-24 yr. [27, 35].…”
Section: Methodsmentioning
confidence: 99%